The thermophysical behaviour of cork supports doped with an innovative thermal insulation and protective coating: A numerical analysis based on in situ experimental data; Energy and Buildings; Vol. 159 - Perilli S. Stefano; Sfarra S. Stefano; Guerrini M. Mirco; Bisegna F. Fabio; Ambrosini D. Dario (2018, 2018)
Title screen